Contract killings by organised crime groups: the spread of deadly violence - Gestel, Barbra van (Organized crime in the 21st century, 2023)
This chapter describes recent developments in the nature of the phenomenon of contract killings by organised crime groups in the Netherlands. The crude and sloppy methods displayed by today’s hitmen can be explained in part by their inexperience, combined with the wide availability of heavy automatic firearms. However, the hitmen’s sloppy work can also be attributed to the methods and management of the principals (who often have a leading role in international drug trafficking). The strict division of tasks in the preparation and execution of contract killings leads to specialisation in subtasks, but it can also lead to miscommunication between ‘spotters’and hitmen. This is particularly true now that hitmen also receive instructions via short text messages. Miscommunication can lead to errors in the actual excecution of a murder, for example the wrong person being asssassinated. Furthermore principals have adopted a crude and intimidating approach that is reflected in the broadening of the target at whom excessive violence is aimed. The extension of deadly violence to wider circles outside the criminal world is a new development in the Netherlands. These murders are not exclusively motivated by the business benefits of resolving a conflict. Assassinations are also ordered for irrational, more emotional reasons with the primary aim of taking revenge, showing power and instilling fear.